2017
DOI: 10.18632/oncotarget.15851
|View full text |Cite
|
Sign up to set email alerts
|

TT genotype of rs2941484 in the human HNF4G gene is associated with hyperuricemia in Chinese Han men

Abstract: The aim of the study is to investigate the association between the human hepatocyte nuclear factor 4 gamma (HNF4G) gene and hyperuricemia in Chinese Han population. A total of 414 hyperuricemia patients and 406 gender and age-matched normouricemic controls were enrolled. Four single nucleotide polymorphisms were genotyped as genetic markers for the human HNF4G gene (rs2977939, rs1805098, rs2941484, rs4735692). Data were analyzed for two separate groups: men and women. For rs2941484, the genotype distribution f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Previous studies described that the mutations in HNF4G gene were not associated with the etiology of diabetes [ 18 , 19 ]. A recent study reported that a polymorphism in HNF4G was associated with hyperuricemia in Chinese Han population [ 20 ]. Recently, Okegawa T et al found that HNF4G expression is significantly elevated in bladder cancer and that HNF4G promotes the growth and invasion of bladder cancer partially by regulating HAS2 [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies described that the mutations in HNF4G gene were not associated with the etiology of diabetes [ 18 , 19 ]. A recent study reported that a polymorphism in HNF4G was associated with hyperuricemia in Chinese Han population [ 20 ]. Recently, Okegawa T et al found that HNF4G expression is significantly elevated in bladder cancer and that HNF4G promotes the growth and invasion of bladder cancer partially by regulating HAS2 [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…HNF4G is a member of the orphan nuclear receptor superfamily (24). In the Chinese Han population, HNF4G polymorphisms are associated with ventilatory disease (25). Wang et al (26) demonstrated that HNF4G acts as an oncogene and can promote the growth and metastasis of lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although we have adjusted these factors in our multivariate model, it is still possible that some underlying confounders have been missed. Some previous similar studies have included blood pressure measures as covariates in the multivariate model 10 , 11 , however, we did not collect these measures, so they were not adjusted in our model. This might introduce some confounding effects on our results.…”
Section: Discussionmentioning
confidence: 99%